Relationship of Acoustic Volume Backscattering of Fish Aggregations and Density of Pelagic Fish in The Waters of Pulau Baai Bengkulu City - Deddy Bakhtiar; Fingki Septiyani; Ari Anggoro (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
The waters of Pulau Baai are unique waters that are closed or protected which have small pelagic fish resources, used as pelagic fishing areas for local fishermen so that they can help the community's economy. One method that can be used to describe the distribution of pelagic fish density is the use of hydroacoustic technology. This study aims to analyze the value of acoustic backscattering (volume backscattering strength, SV) of pelagic fish and associated with the estimation of the density of pelagic fish in the waters of Pulau Baai, Bengkulu City, through in-situ acoustic measurements. The results showed that in the waters of Pulau Baai the highest average SV value was -50.47 dB, which was thought to have a fish density of 2.57 ind/m3 while for a low average SV with a value of -57.48 dB, it was assumed to have a density of 0.04 ind/m3. The density of pelagic fish is acoustically estimated at 26.47 ind/m3 in the water column of Pulau Baai. The SV value affects the estimated fish density by 69% and is categorized as having a high correlation and a positive correlation direction.